'Production efficiency of winter season sunflower (Helianthus annuus) - based cropping systems under Sri Ram Sagar Project command area of Andhra Pradesh - REDDY, M D; KUMAR, K A (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted for 4 years during 1992-93 to 1995-96 to evaluate the production efficiency of6 winter season sunflower (Helianthus annuus L.) • based cropping systems. The sunflower yield equivalents werehigher in sunflower. groundnut (Arachis hypogaea) - greengram (Phaseolus radiatuS L.) cropping system than sunflower- maize (Zea mays L.) - greengrarnj sunflower - sunflower - greengram sunflower- greengram - greengram; sunflower- blackgram (P. mungo L.) - greengram sunflower - sesame (Sesamum indicum L.) - greengram cropping system. Thesunflower - groundnut - greengram cropping system was found to be stable (sustainable yield index 70%) with higherproduction efficiency and net returns compared to other cropping systems. In summer, the sunflower yield equivalentsand sustainable yield index were higher in groundnut than that of other crops grown.